Microglial microvesicles secretion and intercellular signalling - Turola, Elena; Furlan, Roberto; Bianco, Fabio; Matteoli, Michela; Verderio, Claudia (Frontiers in Physiology, 2012)
Microvesicles (MVs) are released from almost all cell brain types into the microenvironment and are emerging as a novel way of cell-to-cell communication. This review focuses on MVs discharged by microglial cells, the brain resident myeloid cells, which comprise approximately 10-12% of brain population. In this review, we summarize first evidence indicating that MV shedding is a process activated by the ATP receptor P2X7 and that shed MVs represent a secretory pathway for the inflammatory cytokine IL-1beta We then discuss subsequent findings which clarify how IL-1beta can be locally processed and released from MVs into the extracellular environment. In addition, we describe the current understanding about the mechanism of P2X7-dependent MV formation and membrane abscission, which, by involving sphingomyelinase activity and ceramide formation, may share similarities with exosome biogenesis. Finally we report our recent results which show that MVs can stimulate neuronal activity, and suggest new areas for future investigation